Targeted Next-Generation Sequencing Combined With Circulating-Free DNA Deciphers Spatial Heterogeneity of Resected Multifocal Hepatocellular Carcinoma - Lin, Jianzhen; Zhao, Songhui; Wang, Dongxu; Song, Yang; Che, Yue; Yang, Xu; Mao, Jinzhu; Xie, Fucun; Long, Junyu; Bai, Yi; Yang, Xiaobo; Zhang, Lei; et al. (Frontiers in Immunology, 2021)
Abstract Background: Hepatocellular carcinoma (HCC) has a high risk of recurrence after surgical resection, particularly among patients with multifocal HCC. Genomic heterogeneity contributes to the early recurrence. Few studies focus on targeted next-generation sequencing (tNGS) to depict mutational footprints of heterogeneous multifocal HCC. Methods: We conducted tNGS with an ultra-deep depth on 31 spatially distinct regions from 11 resected multifocal HCC samples. Matched preoperative peripheral circulating-free DNA (cfDNA) were simultaneously collected. Genomic alterations were identified and compared to depict the heterogeneity of multifocal HCC. Results: Widespread intertumoral heterogeneity of driver mutations was observed in different subfoci of multifocal HCC. The identified somatic mutations were defined as truncal drivers or branchy drivers according to the phylogenetic reconstruction. TP53 and TERT were the most commonly altered truncal drivers in multifocal HCC, while the most frequently mutated branchy driver was TSC2. HCC patients with a higher level of intertumoral heterogeneity, defined by the ratio of truncal drivers less than 50%, had a shorter RFS after surgical resection (HR=0.17, p=0.028). Genome profiling of cfDNA could effectively capture tumor-derived driver mutations, suggesting cfDNA was a non-invasive strategy to gain insights of genomic alterations in patients with resected multifocal HCC. Conclusions: Truncal mutations and the level of genomic heterogeneity could be identified by tNGS panel in patients with resected multifocal HCC. cfDNA could serve as a non-invasive and real-time auxiliary method to decipher the intertumoral heterogeneity and identify oncodrivers of multifocal HCC.